THE IMPACT OF COMPENSATION AND MOTIVATION ON PERFORMANCE OF EMPLOYEES PT. CATUR PARTNER SEJATI SENTOSA IN TANGERANG - Nainggolan, Kaman; M. Daryono, Dadang; Sfenrianto, Sfenrianto; Frieyadie, Frieyadie (www.bsi.ac.id, 2021)
Human resource development is an important factor to achieve the objective of a company to maximize its profit. Theoretically, some factors such as compensation and motivation is closely related to performance of employee of a company. Therefore, the research was conducted to analyses the impact of compensation and motivation on employee performance. The population of this study is all employee, 250 people of PT. Catur Mitra Sejati Sentosa in Tangerang. The samples of this study were the employees of the company totaling of 154 respondents. Multiple regression analysis technique was used to analyses the impact of compensation and motivation on employee performance. The results of this research showed that compensation and motivation have a positive and significant impact on employee performance. This implies that the company should focus on improving compensation and motivation in order to increase the performance of employees.